A unified integral interpretation of thermal analysis data (2016)
(Eng) Most integral methods for thermal analysis data use linear regressions based on some approximate representation of the temperature integral. But this approach is inconvenient because there are many approximations and each one can produce a different result for the same data set. This work shows how to reduce the search of kinetic parameters to a non-linear regression calculating the temperature integral through the incomplete gamma function. In this way the use of approximations is avoided and dependence of the preexponential factor on temperature can be included in the model. An isoconversional analysis of a data set available in the literature is used to explain the proposed method.